Global prevalence and antibiotic resistance in clinical isolates of Stenotrophomonas maltophilia: a systematic review and meta-analysis - Banar, Maryam; Sattari-Maraji, Azin; Bayatinejad, Ghazal; Ebrahimi, Elahe; Jabalameli, Leila; Beigverdi, Reza; Emaneini, Mohammad; Jabalameli, Fereshteh (Frontiers in Medicine, 2023)
Introduction Stenotrophomonas maltophilia is a little-known environmental opportunistic bacterium that can cause broad-spectrum infections. Despite the importance of this bacterium as an emerging drug-resistant opportunistic pathogen, a comprehensive analysis of its prevalence and resistance to antibiotics has not yet been conducted. Methods A systematic search was performed using four electronic databases (MEDLINE via PubMed, Embase, Scopus, and Web of Science) up to October 2019. Out of 6,770 records, 179 were documented in the current meta-analysis according to our inclusion and exclusion criteria, and 95 studies were enrolled in the meta-analysis. Results Present analysis revealed that the global pooled prevalence of S. maltophilia was 5.3 % [95% CI, 4.1–6.7%], with a higher prevalence in the Western Pacific Region [10.5%; 95% CI, 5.7–18.6%] and a lower prevalence in the American regions [4.3%; 95% CI, 3.2–5.7%]. Based on our meta-analysis, the highest antibiotic resistance rate was against cefuroxime [99.1%; 95% CI, 97.3–99.7%], while the lowest resistance was correlated with minocycline [4·8%; 95% CI, 2.6–8.8%]. Discussion The results of this study indicated that the prevalence of S. maltophilia infections has been increasing over time. A comparison of the antibiotic resistance of S. maltophilia before and after 2010 suggested there was an increasing trend in the resistance to some antibiotics, such as tigecycline and ticarcillin-clavulanic acid. However, trimethoprim-sulfamethoxazole is still considered an effective antibiotic for treating S. maltophilia infections.